A control technique for compensating the effects of input voltage variations on matrix converter modulation algorithms - Sünter, S; Altun, H; Clare, JC (Taylor & Francis Inc, 2002)
Many of the existing algorithms for the matrix converter are formulated in a way that makes their practical incorporation into the closed-loop control scheme difficult. cult. Since these algorithms make assumptions about the input voltage for generating the switching actuation signals, it is not possible to compensate the input voltage variations, which result in incorrect voltage waveforms being applied to the load. In this article, a novel control technique for compensating the effects of the input voltage variations on the matrix converter algorithms is described. Simulation and experimental results demonstrating the performance of the proposed control algorithm are presented.
Keywords: matrix converter; compensation; system simulation; induction motor